Haiti : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
Fiscal policy in Haiti should be oriented toward more developmental objectives. Steps have been taken in sustaining inclusiveness; however, the current taxation and expenditure frameworks do not completely fulfill the necessary requirements for these objectives. Inefficient public investment and lack of transparency have resulted in lower growth, lower fiscal revenue, and higher costs as well as macroeconomic imbalances, limited competitiveness, and slow economic integration. The country should take advantage of the available financial assistance and step up efforts to improve public investment quality.